(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the current study, an effort has been made to identify socio-economic inequalities in rural Haryana during the post-reform period. Secondary data has been used in this study to quantity socioeconomic inequalities in rural Haryana. The socio-economic gaps in rural Haryana have been quantified using secondary data from the Census of India (2011). Numerous factors, including social and economic indicators, are used to analyse the regional disparities in socio-economic development levels. The ultimate outcome has been determined using a composite index development technique. All districts have been divided into three categories based on their development indexes, high, medium, and low. Three of the state’s twenty-one districts (Fatehabad, Hisar, Sirsa) had high socio-economic development, fifteen district (Ambala, Bhiwani, Faridabad, Jhajjar, Jind, Kaithal, Karnal Kurukshetra, Palwal, Panchkula, Panipat, Rewari, Rohtak, Sonipat, Yamunanagar) had medium socio-economic development, and three district (Mahendergarh, Gurgaon, Mewat) had low socio-economic development.